Wireless piezoelectric strain sensing measurement using a frequency modulation technique. (June 2015) - Yoon, Hwan-Sik; Kim, Se-hun; Kim, Min-Hyuck; Jung, Dongsoo; Kim, Joo-Hyung; Kim, Hyeon-Ju; Lee, Ho-Saeng
A simple wireless strain sensor using a frequency modulation technique is presented. The sensor employs a piezoelectric transducer that produces electric voltage as it is mechanically strained. When the piezoelectric sensor is connected to a single-transistor frequency modulation circuit, the sensor output voltage causes the modulation circuit frequency to shift. This modulated signal is then wirelessly transmitted to a remote station, where a demodulation circuit retrieves the buried strain measurement data in real time. Using this technique, a dynamic strain measurement is possible without any wire connection between the sensing point and the monitoring station. In order to demonstrate the performance of the wireless strain sensor and the measurement system, a wireless measurement of a vibrating cantilevered beam is experimentally conducted. This type of sensor has numerous applications in the strain or vibration measurement of moving or rotating structures such as turbo machinery.